2020
DOI: 10.51593/20200001
|View full text |Cite
|
Sign up to set email alerts
|

Trends in U.S. Intention-to-Stay Rates of International Ph.D. Graduates Across Nationality and STEM Fields

Abstract: Policymakers continue to debate the ability of the United States to attract and retain top international talent. This Issue Brief assesses how many international Ph.D. graduates across various STEM fields and nationalities intend to stay in the United States after completing their degrees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This study has important implications for global academic mobility, because Chinese citizens not only account for a large share of the US and EU STEM PhD graduates but also are among the most productive graduates (5). As China continues to invest in higher education and academic talent, we can expect more Western-trained Chinese students to return to China, although findings were mixed; whereas a National Science Foundation survey showed that 87% of Chinese STEM PhDs wanted to stay in the US (15), another study revealed that 70% of them would prefer to return to China if offered salaries comparable to what they could expect to receive in the US (17). We can also expect Chinese universities to become more attractive locations for Chinese (and international) students intending to pursue scientific research careers-students who would otherwise study in the US or EU.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 95%
See 1 more Smart Citation
“…This study has important implications for global academic mobility, because Chinese citizens not only account for a large share of the US and EU STEM PhD graduates but also are among the most productive graduates (5). As China continues to invest in higher education and academic talent, we can expect more Western-trained Chinese students to return to China, although findings were mixed; whereas a National Science Foundation survey showed that 87% of Chinese STEM PhDs wanted to stay in the US (15), another study revealed that 70% of them would prefer to return to China if offered salaries comparable to what they could expect to receive in the US (17). We can also expect Chinese universities to become more attractive locations for Chinese (and international) students intending to pursue scientific research careers-students who would otherwise study in the US or EU.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 95%
“…We also find that few top-caliber scientists have availed themselves of this program, suggesting room for improvement in Chinese research institutions. With the option to pursue independent research either in the US or in China, top-caliber expatriates remain unlikely to return even given the YTT offers, probably reflecting a social and cultural environment conducive to scientific inquiry in the US (15). The departure of Chenyang Xu-a YTT recruit and a Breakthrough Prize winner in mathematics-back to the US has specifically raised questions about whether a research environment distinguished by administrative interventions and personal connections could be conducive to nurturing top-caliber scientists (7)(8)(9).…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…For instance, 75 percent of South Korean doctoral students who received their degrees from U.S. institutions between 2012 and 2017 indicated they planned to stay in the United States after graduation. 93 South Korea has also struggled to attract foreign-born talent. In 2015, for example, the government issued just under 20,000 E-7 high-skill work visas.…”
Section: Challenges In Attracting and Developing Ai Talentmentioning
confidence: 99%